DESCRIPTION OF THE ROLE OF GUIDING BOOK IN LEARNING BASED ON ASSESSMENT AS LEARNING - Muchlis Muchlis; Rudiana Agustini; Kusumawati Dwiningsih; Findiyani Ernawati Asih (JCER (Journal of Chemistry Education Research), 2022)
Abstract. The  aim of this research was to describe the Guiding Book which helps implementing assessment as learning. The research subjects were 29 students of Undergraduate Program of Chemistry Education, Universitas Negeri Surabaya. The research methods were questionnaire and documentation method. Questionnaire method was to record student responses to the role of the Guiding Book which helps implementing assessment as learning. The documentation method was to record students’ activity in implementing of learning based on assessment as learning. The document used in this documentation method which was  assessment as learning based worksheet. The result showed that the percentage of students response was about 81% for the six items, which means that the Guiding Book played a very helpful role in the implementing  of learning based on assessment as learning. The result of observations on assessment as learning based worksheet showed that students implemented of learning based on assessment as learning by utilizing or being inspired the contents of the Guiding Book. Keywords: guiding book, assessment as learning